Social Barriers for the Use of Available and Accessible Public Green Spaces - Noël, Charlotte; Landschoot, Lisa Van; Vanroelen, Christophe; Gadeyne, Sylvie (Frontiers in Sustainable Cities, 2021)
Background: Our living environment impacts on our health and wellbeing. The physical and mental benefits of interaction with nature and the ecosystem are well-established in literature. From a public health perspective, it is thus crucial that people make use of public green spaces (PGSs) in urban areas. Therefore, it is important to understand why they are potentially under-used. Methods: In this research we identified social barriers that prevent the (full) use of PGSs in the Brussels Capital Region (BCR). We applied a qualitative research methodology. Insights were generated through 51 individual face-to-face in-depth interviews with a group of PGS-users diversified in terms of age, gender, migration background and socio-economic situation. Questions were open-ended and the interview guide was semi-structured. Results: Our research identified three social barriers for the use of available and accessible PGSs: 1) perceived dangers due to bad precedents, the presence of socially frightening elements or a lack of social control, 2) not feeling in place because of the dominance of a specific group of users or because of community perceptions and 3) not fulfilling one’s social needs. These barriers were different in their manifestations (barriers to go – barriers to stay – barriers for integral use) and resulted in a differential degree of PSG-use. We distinguished three different dimensions of the completeness or integrality (understood as full or optimal use) by which PGSs are used; the spatial integrality (using all the different parts of the PGS), the temporal integrality (using PGSs at all moments of the day) and the social integrality of PGS-use (without any restriction concerning social interaction). Conclusions: While there are many benefits associated with PGSs, a continuous social evaluation of these physical places might generate social barriers resulting in a decline of their use, a more superficial use or even in complete avoidance. Both the social context and social needs of individuals result in specific social barriers.